Fish Allergens at a Glance: Variable Allergenicity of Parvalbumins, the Major Fish Allergens - Kuehn, Annette; Swoboda, Ines; Arumugam, Karthik; Hilger, Christiane; Hentges, François (Frontiers in Immunology, 2014)
Fish is a common trigger of severe, food-allergic reactions. Only a limited number of proteins induce specific IgE-mediated immune reactions. The major fish allergens are the parvalbumins. They are members of the calcium-binding EF-hand protein family characterized by a conserved protein structure. They represent highly cross-reactive allergens for patients with specific IgE to conserved epitopes. These patients might experience clinical reactions with various fish species. On the other hand, some individuals have IgE antibodies directed against unique, species-specific parvalbumin epitopes, and these patients show clinical symptoms only with certain fish species. Furthermore, different parvalbumin isoforms and isoallergens are present in the same fish and might display variable allergenicity. This was shown for salmon homologs, where only a single parvalbumin (beta-1) isoform was identified as allergen in specific patients. In addition to the parvalbumins, several other fish proteins, enolases, aldolases and fish gelatin, seem to be important allergens. New clinical and molecular insights advanced the knowledge and understanding of fish allergy in the last years. These findings will be useful for the advancement of the IgE-based diagnosis but also for the management of fish allergies consisting of advice and treatment of fish-allergic patients.